Cross-sectional assessment of the periapical status as related to quality of root canal fillings and coronal restorations in a Yemeni population. - Madfa, Ahmed; Al-Hamzi, Mohsen; Senan, Elham (University of Concepci?n in Chile, 2017)
Aim: The present study aimed to examine the influence of the quality of root canal fillings and coronal restorations on the prevalence of periapical lesions. Materials and Methods: Two hundred digital panoramic radiographs were obtained from the archive of Al?HamziDental Center in Sanaa, Yemen. The final sample consisted of 120 radiographs, and 675 root filled teeth.The quality of root canal fillings was scored according to criteria of length, homogeneity and taper. Coronal status (type of restoration, signs of marginal leakage or decay) was also evaluated. The periapical status was categorized on the basis of presence or absence of radiographical signs of apical periodontitis. Chi-square test was used to determine statistical significance between different parameters. Results: We found that 93.6% of root filled teeth were associated with apical periodontitis. Only 9.2% of root filled teeth were found to have an acceptable standard of root canal fillings, of which 32.3% was also associated to signs of periapical disease. In roots with an unacceptable root canal filling, 95.4% had periapical disease. Teeth with good (14.4%) and poor (32.9%) intra-coronal restorations had apical periodontitis in 93.8% and 97.7% of cases, respectively. Crown restorations were present in 52.7% of root filled teeth, of which 91.0% were associated with periapical lesions. Conclusion: The poor technical quality of root canal fillings and coronal restorations is consistent with a high revalence of apical periodontitis.